Caracterización morfológica y faneroptica de las razas caprinasen la provincia de Santa Elena. Quevedo - Chevez Arias, Javico Hipólito (2013)
This work allowed to estimate the levels of the phenotypic variability of the goats as objectives was to characterize the goat races in the province of Santa Elena Peninsula in its morphological aspects and faneropticas, which will provide the information necessary to address a conservation plan based on sustainable development and determine if there are differences structural morph between them. 174 Female goats that were 20 measures structural morph and five faneropticas were evaluated for this. The results obtained indicate that there are significant differences with a degree of homogeneity of medium-high with a coefficient of variation of 10.07 to 85.72% among the population in the morph structural characteristics such as length of the body (LC); Height back sternal (ALP), thoracic perimeter (Pt); Back to the belly (PA) perimeter; Width of the Croup (AG); Length of the rump (LG); Bottom width of the Croup (AIC); Width of chest (AP); Height to the sternum (HS); Width of the head (AC); Length of the head (ACL); Length of the ear (it); Width of the ear (AO); Length of the cervical (LSC); Length of neck (SCI); Width of the neck with the head (AAC) and width of the neck on the back side (APC) and on the other hand also through coefficients for the length of the trunk (LT) variability, boosted to the cross (ACR) and height to the hip (ALC) which does not exceed 8% no difference with a degree of homogeneity between low. A greater percentage of pigmentation in black mucosa was observed in the characters faneropticos (69.54%) and in another as the rosy was (24.14%), prevailed also pigmentation of the color black hoof (62.07%), hair length form was the short (89.66%), characteristic of the coating (62.07%) and number of color was one only with (61.49. The layer color reported 14 colors, the most common variants (87.36%) are based on the red fur. It is concluded that these results allow to select animals differentially for organizing herds of different productive purposes without incorporating foreign breeds in this province......